2016
DOI: 10.4209/aaqr.2015.06.0391
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Universal “Baseline” Characterisation of Air Masses for High- and Low-Altitude Observing Stations Using Radon-222

Abstract: We demonstrate the ability of atmospheric radon concentrations to reliably and unambiguously identify local and remote terrestrial influences on an air mass, and thereby the potential for alteration of trace gas composition by anthropogenic and biogenic processes. Based on high accuracy (lower limit of detection 10-40 mBq m -3 ), high temporal resolution (hourly) measurements of atmospheric radon concentration we describe, apply and evaluate a simple two-step method for identifying and characterising constitue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 57 publications
2
48
0
Order By: Relevance
“…Figure 2 also shows that fetch-component radon concentrations begin to drop in both years around September-October, which HYSPLIT trajectories show is coincident with air mass origin shifting away from the Australian continent and towards the northern Arafura and Timor seas. Throughout the wet season fetch-component radon remains low, though not at baseline levels (Zahorowski et al, 2013;Chambers et al, 2016b), implying that there is still some terrestrial influence on incoming air masses from the Australian continent or surrounding islands to the north. Wetseason wind data (Fig.…”
Section: Overall Means and Seasonal Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 also shows that fetch-component radon concentrations begin to drop in both years around September-October, which HYSPLIT trajectories show is coincident with air mass origin shifting away from the Australian continent and towards the northern Arafura and Timor seas. Throughout the wet season fetch-component radon remains low, though not at baseline levels (Zahorowski et al, 2013;Chambers et al, 2016b), implying that there is still some terrestrial influence on incoming air masses from the Australian continent or surrounding islands to the north. Wetseason wind data (Fig.…”
Section: Overall Means and Seasonal Trendsmentioning
confidence: 99%
“…Originally an experimental radar site, ATARS was expanded in 2010 to incorporate greenhouse gas measurements as part of the Australian Greenhouse Gas Observation Network (Ziehn et al, 2016) and is operated jointly by the Australian Bureau of Meteorology (BoM) and the Commonwealth Science and Industrial Research Organisation (CSIRO). The Australian Nuclear Science and Technology Organisation (ANSTO) began continuous atmospheric radon measurements at the site in 2012 to aid in the determination of terrestrial influence on observed air masses (Chambers et al, 2016b). In June 2014, an additional expansion took place and now continuous aerosol, reactive gas (O 3 , NO x ), and GEM measurements complement the suite of atmospheric measurements at the site (Mallet et al, 2016).…”
mentioning
confidence: 99%
“…If these two regimes are well disaggregated, the available data sets can represent more reliable information about long-term changes of undisturbed atmospheric GHG levels, or investigate local and regional GHG sources and sinks when specifically analyzing the deviations from the baseline conditions. In this study, the baseline conditions refer to a selected subset of data from the validated data set, representing well-mixed air masses with minimized short-term external influences (Elliott, 1989;Calvert, 1990;Balzani Lööv et al, 2008;Chambers et al, 2016). 10 Measurement results depend on sampling methods, analytical instrumentation and data processing.…”
Section: Introductionmentioning
confidence: 99%
“…Since the majority of anthropogenic pollution sources are of terrestrial origin, there is typically a close correspondence between radon concentration and atmospheric pollutants, or other natural trace species with terrestrial origins (e.g., Chambers et al, 2016). Consequently, the most reliable estimates of background pollution levels are usually derived from air masses that have had the least recent land contact.…”
Section: Characterising "Background" Pollution Concentrationsmentioning
confidence: 99%